Perception and Impact of COVID-19 Pandemic in Psoriasis Patients: Data from the German PsoBest and the CoronaBest Registries - Valencia López MJ; Stephan B; Meineke A; Wolf S; Thaci D; Mrowietz U; Andrees V; Rustenbach SJ; Reich K; Thalmann L; Bogena H; Staubach P; et al. (Dove Medical Press, 2024)
María José Valencia López,1,* Brigitte Stephan,1,* Anna Meineke,1 Sandra Wolf,1 Diamant Thaci,2 Ulrich Mrowietz,3 Valerie Andrees,1 Stephan Jeff Rustenbach,1 Kristian Reich,1 Linus Thalmann,1 Henriette Bogena,1 Petra Staubach,4 Ralph Michael von Kiedrowski,5 Matthias Augustin1 1Institute for Health Services Research in Dermatology and Nursing (IVDP), University Medical Center Hamburg-Eppendorf (UKE), Hamburg, Germany; 2Institute and Comprehensive Center for Inflammation Medicine, University of Lübeck, Lübeck, Germany; 3Psoriasis-Center, Department of Dermatology, University Medical Center Schleswig-Holstein, Kiel, Germany; 4Department of Dermatology and Allergy, University Medical Center Mainz, Mainz, Germany; 5Dermatological Practice Selters, Selters, Germany*These authors contributed equally to this workCorrespondence: Matthias Augustin, Institute for Health Services Research in Dermatology and Nursing (IVDP), University Medical Center Hamburg-Eppendorf (UKE), Martinistraße 52, Hamburg, 20246, Germany, Tel +49 040 7410 55428, Fax +49 040 7410 55348, Email m.augustin@uke.deBackground: Limited data are available characterizing the impact of the SARS-CoV-2 pandemic on psoriasis care for patients in Germany.Objective: To analyze patient perception and impact of the pandemic on well-being and psoriasis management of German patients with moderate-to-severe psoriasis or psoriasis arthritis under systemic therapies.Methods: The CoronaBest registry captures events of SARS-CoV-2 infections and analyzes the impact of the pandemic on patients with psoriasis or psoriasis arthritis. In June 2020, and independently in February 2022, patients with psoriasis or psoriasis arthritis received a standardized questionnaire for current treatment, protective measures, well-being, and individual risks for COVID-19, among others.Results: Included were 4,194 patients in 2020 (mean age of 47.7 years and 41.8% women) and 4,818 patients in 2022 (mean age of 56.4 and 42.9% women). Treatment discontinuations were observed in 2.7% and 1.7% of patients in 2020 and 2022, respectively. In the vast majority of the cases (> 92%), no additional measures were taken concerning the management of psoriasis treatments in either 2020 or 2022. Those patients with changes reported most frequently: telephone calls instead of face-to-face visits (80.2%, in 2020 vs 40.5% in 2022) or more frequent controls (27.1%, 2020 vs 22.0%, 2022). A majority (66.7%, 2020, and 70.6%, 2022) did not perceive the virus as a considerable threat. The proportion of patients feeling well informed about COVID-19 by physicians increased from 42.6% in 2020 to 51.8% in 2022. About 81.1% of patients in 2020 and 67.5% in 2022 stated that their overall personal condition was not affected due to the pandemic. Physicians attributed no special risk of contracting SARS-CoV-2 in most of the patients.Conclusion: A high rate of systemic treatment persistence and awareness of risks and protective measures indicate that health care for psoriasis largely followed current national and international recommendations during the COVID-19 pandemic.Keywords: psoriasis, COVID-19, SARS-CoV-2, pandemic, patient perception, risk factors